Automation of library preparation using Illumina ForenSeq kit for routine sequencing of casework samples. (December 2017) - Laurent, F.X.; Ausset, L.; Clot, M.; Jullien, S.; Chantrel, Y.; Hollard, C.; Pene, L.
Abstract: Massively Parallel Sequencing (MPS) technologies are called upon to play a major role in forensic genomics in the next few years. However, library preparation protocols contain numerous steps which can complexify casework analysis in routine. Implementation of a MPS analytical workflow, in a casework laboratory, requires automation to guarantee a full sample tracking and to minimize contamination risks. In this study, we present the development and validation of a fully automated workflow using Illumina ForenSeq DNA signature Prep Kit on a NGS STARlet HID Illumina platform. Automation greatly helps with library preparation reproducibility and significantly reduces hands-on time. We are confident that automation of MPS technologies will enhance forensic laboratory to adopt these powerful analytical tools determinant for the future of the forensic genomics field.